2014
DOI: 10.3748/wjg.v20.i48.18240
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor and cancer stem cells in hepatitis C virus-associated liver disease

Abstract: CTC counts and AFP, CK19, telomerase, and MAGE1/MAGE3 expression predict disease progression in patients with HCV, whereas telomerase, MAGE3, CD90, CD133 and CK19 are prognostic markers in HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…9 studies [22,28,31,[38][39][40][41][42][43] (Fig. 4B), the between-study heterogeneity was moderate (I 2 =33%, p = 0.16).…”
Section: Correlation Of Circulating Tumor Cells With Clinicopathologimentioning
confidence: 99%
“…9 studies [22,28,31,[38][39][40][41][42][43] (Fig. 4B), the between-study heterogeneity was moderate (I 2 =33%, p = 0.16).…”
Section: Correlation Of Circulating Tumor Cells With Clinicopathologimentioning
confidence: 99%
“…An increasing number of studies have shown that CD90, which is expressed by hepatic stem/progenitor cells during liver development, could be used as a marker for human LCSCs and as a target for the diagnosis and therapy of hepatocellular carcinoma (HCC). [10][11][12] Therefore, CD90 + LCSCs are referred to as CD90 + LCSCs in this study. Relapse and metastases can occur if the applied treatments fail to remove cancer stem cells (CSCs); therefore, therapies that eliminate CSCs may be more effective than current drugs that target proliferating non-CSCs in the treatment of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the CD90 stem cell marker has been identified as a prognostic marker for high-grade gliomas, and CD44 has been shown to be a potential metastatic marker [28, 29]. Bahnassy and colleagues [30] have shown that aberrant expression of cancer stem cell markers (CD133, CD90 and CD44) contributes to tumor progression. In fact, according to our in vivo results, the CD133+/CD90+/CD44+ tumor stem cells may be responsible for dissemination of glioblastoma, which leads to reduced patient survival [30].…”
Section: Discussionmentioning
confidence: 99%
“…Bahnassy and colleagues [30] have shown that aberrant expression of cancer stem cell markers (CD133, CD90 and CD44) contributes to tumor progression. In fact, according to our in vivo results, the CD133+/CD90+/CD44+ tumor stem cells may be responsible for dissemination of glioblastoma, which leads to reduced patient survival [30]. The glioblastoma CD133 + cells also co-express significant levels of SSEA-3 (stage-specific embryonic antigen 3), Mush-1 (neural stem cell marker) and Nanog (transcriptional regulator involved proliferation and self-renewal of embryonic stem (ES) cells).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation